Optimalisasi Pelayanan Publik dalam Pembuatan Surat Keterangan Tidak Sedang Menjalani Hukuman Pidana Penjara di Kejaksaan Negeri Karawang Pada Masa Pandemi Covid-19 - Gheanina Bella Pravillia; Maulana Rifa’i; Gun Gun Gumilar (Peneliti.net, 2022)
This study aims to examine the optimization of public services in making a certificate not currently serving a prison sentence at the Karawang District Attorney during the Covid-19 pandemic using the Lovelock and Wright Service Quality theory (2002: 266-267) in which there are five variable dimensions. includes Reliability, Tangibility, Responsiveness, Assurance and Assurance and Empathy. This study used descriptive qualitative method. The data collection technique was carried out through triangulation which included interviews, observations and documentation studies, then the data that had been obtained were analyzed through three stages, namely data reduction, data presentation and conclusion drawing. The results of the discussion show that making a certificate is not currently serving a prison sentence at the Karawang District Prosecutor's Office during the Covid-19 pandemic not optimal in the dimensions of Reliability, Tangibility, Responsiveness, and Empathy, this is evidenced by the delay in performance, lack of information and the implementation of work from houses by employees of the Karawang District Prosecutor's Office as well as the focus on other urgent problems to be resolved. As for the dimensions of guarantee and certainty of service quality in making a certificate of not serving a prison sentence at the Karawang District Attorney during the Covid-19 pandemic, it can be said to be quite optimal because of their polite attitude towards every community.